Glass formation, physical and structural investigation studies of the (90-x) Sb2O3-10WO3-xNaPO3 glasses. (March 2022) - Guesmia, Nesrine; Hamzaoui, Majda; Beghdadi, Lina; Soltani, M.T.; de Ligny, D.
Abstract: The new series of SWN glasses were examined with the formula (90–x) Sb2 O3 –10WO3 –xNaPO3 glasses (x ranging from 10 to 70). Certain thermal, physical, mechanical, and structural properties have been tested. The DSC curves confirmed the glassy nature as well as the thermal stability of our glasses. The Vickers hardness, modulus of elasticity and Raman spectroscopy were put to the test. The increase in elastic moduli and physical characteristic parameters is associated with an increase in the stiffness and a change in the structural network of the glass system with the addition of NaPO3 content by the forming of a P-O-M bridge (M=P, Sb or W), which increases the network connectivity and contributes to an increase in the glass transition temperature and elasticity modulus. This could be due to the polymerization of the glass network as a result of the high concentration of PO4, which acts as a bridge between them and is confirmed by Raman spectroscopy. To establish the similarity between the theoretical and observed results of elastic moduli and Poisson's ratio in our glasses, Mackenzie's Makishima theory was used. Our system has many colors (yellow, blue, transparent), which are related to an increase (reduction) or decrease (oxidation) in the number of electrons in the atomic system of such materials.